Molecular characterization of Quercus suber MYB1, a transcription factor up-regulated in cork tissues - Almeida, Tania
The molecular processes associated with cork development in Quercus suber L. are poorly understood. A previous molecular approach identified a list of genes potentially important for cork formation and differentiation, providing a new basis for further molecular studies. This report is the first molecular characterization of one of these candidate genes, QsMYB1, coding for an R2R3-MYB transcription factor. The R2R3-MYB gene sub-family has been described as being involved in the phenylpropanoid and lignin pathways, both involved in cork biosynthesis. The results showed that the expression of QsMYB1 is putatively mediated by an alternative splicing (AS) mechanism that originates two different transcripts (QsMYB1.1 and QsMYB1.2), differing only in the 5'-untranslated region, due to retention of the first intron in one of the variants. Moreover, within the retained intron, a simple sequence repeat (SSR) was identified. The upstream regulatory region of QsMYB1 was extended by a genome walking approach, which allowed the identification of the putative gene promoter region. The relative expression pattern of QsMYB1 transcripts determined by reverse transcription quantitative polymerase chain reaction (RT-qPCR) revealed that both transcripts were up-regulated in cork tissues; the detected expression was several times higher in newly formed cork harvested from trees producing virgin, second or reproduction cork when compared with wood. Moreover, the expression analysis of QsMYB1 in several Q. suber organs showed very low expression in young branches and roots, whereas in leaves, immature acorns or male flowers, no expression was detected. These preliminary results suggest that QsMYB1 may be related to secondary growth and, in particular, with the cork biosynthesis process with a possible alternative splicing mechanism associated with its regulatory function. (C) 2012 Elsevier GmbH. All rights reserved.